Permanent education throughout life as the aim and result - Nadezhda N. Elhova; Evgeny V. Krotov; Raisa B. Rudakova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The modern characteristics of the labor market are its instability and uncertainty, so the constant development and self-development of a specialist, his professional growth is a necessity. One of the most important documents in the legal framework defining the sphere of education in the Russian Federation emphasizes the training and retraining of specialists for most sectors of economic and social development. The priority is the requests of modern youth for highly gualified and growing demands for educational services, focusing on the direction of training and retraining of scientific teaching staff because the training of specialists of various specialties and areas of professional activity degends on them. The young people today have the opportunity to choose an educational organization. The system of additional professional education was more popular, as it provides an opportunity for professional self-improvement, and getting a new specialty, carrying out the process of continuous professional self-determination, based on the "education throughout life". All this is an undeniable advantage of additional professional educationPermanenteducation helps to change the nature of interaction from the position of "Student- Teacher" to the position of "TEACHER of the FUTURE" such as digital, inspiring, knowledgeable, enthusiastic, guardian of wisdom - "STUDENT of the FUTURE" as self-managed. The article proposes a structural and functional model of education of the future, which provides everyone with the opportunity to choose an individual educational trajectory as an institutionalized support for learning and development throughout life.